The trading crowd an ethnography of the Shanghai stock market - Hertz, Ellen (Cambridge University Press, 1998)
In 1992, there was an explosion of 'stock fever' in Shanghai. 'From the moment I set foot in Shanghai until my last day there, people from all walks of life wanted to talk to me about the market', Ellen Hertz writes. Her 1998 study sets the stock market and its players in the context of Shanghai society, and it probes the dominant role played by the state, which has yielded a stock market very different from those of the West. A trained anthropologist, she explains the way in which investors and officials construct a 'moral storyline' to make sense of this great structural innovation, identifying a struggle between three groups of actors - the big investors, the little investors, and the state - to control the market
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Shanghai-Zhengquan-Jiaoyisuo; Stock exchanges / China / Shanghai; Ethnosoziologie